Interaction of an easterly system with a westerly system and its associated weather over southern Peninsula - LAKSHMINARAYANAN, R. (MAUSAM, 1998)
During the week 11-17 April 1996 southern Peninsula received good rainfall especially with heavy rainfall on 13 and 15 April 1996 in Tamilnadu making the seasonal rainfall from 1 March to 17 April 1996 into large excess in south interior Kamataka and excess in Tamilnadu and north interior Kamataka. In this paper. an attempt is made to investigate in the synoptic situations leading to the large excess rainfall over these areas during the week 11- 17 April 1996.